1998
DOI: 10.1176/ajp.155.7.947
|View full text |Cite
|
Sign up to set email alerts
|

Guided Self-Change for Bulimia Nervosa Incorporating Use of a Self-Care Manual

Abstract: Guided self-change incorporating use of a self-care manual offers an approach that can be as effective as standard cognitive behavior therapy in the long term and can considerably reduce the amount of therapist contact required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 26 publications
5
60
1
2
Order By: Relevance
“…Therefore, fortnightly sessions were also employed where necessary. It would be interesting to find out whether behaviors would have continued to improve over a longer follow-up period as has been demonstrated by other GSH studies (Thiels et al, 1998), especially as our results indicate that attitudes continue to improve at the 3-month follow-up.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Therefore, fortnightly sessions were also employed where necessary. It would be interesting to find out whether behaviors would have continued to improve over a longer follow-up period as has been demonstrated by other GSH studies (Thiels et al, 1998), especially as our results indicate that attitudes continue to improve at the 3-month follow-up.…”
Section: Discussionsupporting
confidence: 61%
“…Table 1 presents the clinical features for the 20 participants at initial interview. This cohort appears to be typical of patients with BN who have been treated in other studies (e.g., Thiels et al, 1998). The male participant had a higher current BMI (37.81) and a higher lowest BMI (24.07) than the group, but was otherwise unremarkable.…”
Section: Participant Characteristicsmentioning
confidence: 65%
See 1 more Smart Citation
“…A number of investigations have demonstrated the efficacy of self-help and mininal intervention approaches with BN, including the use of a self-help manual along with supportive phone calls (Huon, 1985) or brief supervision sessions (Cooper et al, 1994;Cooper, Coker, & Fleming, 1996). In controlled trials of BN, self-help manuals used with brief supervisory sessions have been found to be as efficacious as standard cognitive-behavioral therapy (CBT; Thiels, Schmidt, Treasure, Garthe, & Troop, 1998;Treasure et al, 1994Treasure et al, , 1996. A self-help manual has also been shown to produce improvement in symptoms comparable to fluoxetine (Mitchell et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…These results are equivalent to those obtained by using individual CBT. This study was replicated in Germany with a sample of 62 who were followed up for 6 months to 2 years (Thiels et al, 1998). Both groups achieved significant improvement in a range of measures.…”
mentioning
confidence: 93%